Ons wag op die kaptein (Elsa Joubert): Bybel en Christendom as intertekste - M. J. Prins (Literator, 1993)
The Bible and Christianity are the most important intertexts in the novels of Elsa Joubert. The purpose of this article is to examine the part played by these intertexts in Ons wag op die kaptein. To this end the relationship between certain passages of Scripture as well as some basic beliefs of Christianity and aspects of the novel are examined: the theme, Ana-Paula's attitude towards the people of Africa as well as to her white subordinates, Carlos' treatment of his labourers, the significance of the arrival of the ‘captain' and the reconciliation which takes place during the very last moments before this arrival. Finally a brief look is taken at the link between the above-mentioned intertexts and some of the leading motifs in the narrative.